PENGARUH FAKTOR KOGNITIF/ PENGETAHUAN, PSIKOMOTORIK/ KETRAMPILAN DAN AFEKTIF/ SIKAP TERHADAP PENINGKATAN MINAT BERTANI - Suprapto, Adi; Yektiningsih, Endang; Priyanto, Eko (Berkala Ilmiah AGRIDEVINA, 2017)
The purpose of this study is 1. Identify characteristics of elementary students (SD) infollowing the skills of farming skills. 2. Analyze the influence of cognitive / knowledgefactor, psychomotor / skill and affective / attitude toward increasing interest in farming.The method used in the sampling is saturated or census sampling. Data analysis used wasdescriptive analysis and Differentiation Analysis, different test to know the effect of farmskill training on student interest in farming. The results showed that the average age ofgrade 3 students in elementary and non-elementary school was 8.73 years and 8.87 yearsin the low class that tended to adhere to the rules. Gender of respondents of elementaryschool-based elementary students is dominated by female students while nonenvironmentalbasilic elementary students are dominated by male students. girls arefaster to master language than boys, So girls are more likely to understand and captureagricultural training materials than boys. Employment of parents respomden of PrimarySchool-based Elementary students most work as factory workers while Non-EnvironmentBased Non School students are most employed as merchants. In addition, results basedon t-test farming skills have a positive effect on students' interest in farming. There is asignificant difference in the student's interest in farming using a farming skills trainingmethod.